Improving Students’ Reading Comprehension Using Fairy Tale Story at SMP Negeri 5 Lirung, Talaud Regency.: Reading, Skills, Fairy Tale Story, Eight Grade Students. - Matei, Agneria; Pelenkahu, Noldy; Hampp, Paula (Program Studi Pendidikan Bahasa Inggris, 2024)
English may be an all-inclusive dialect since it is utilized by most countries worldwide as the essential dialect. Dialect may be a communication instrument organized in units, such as words, bunches of words, clauses, and sentences communicated orally or in composing. Dialect is an extreme expression used to communicate something to others.This Research aimed to see the effectiveness of using fairy tales to improve student’s reading skills in the eighth grade of SMP Negeri 5 Lirung. This Research used a pre-experimental design with two groups, pre-test and post-test. This Research showed that Fairy Tale Story effectively improved students’ reading skills. The result showed that the post-test was higher than the pre-test. The mean score of the pre-test was 73.26, and the mean score of the post-test was 83.69, which means that the result of the post-test was higher than the pre-test. It can be stated that students’ reading skills in eighth grade of SMP Negeri 5 Lirung were high in the post-test. So it means Fairy Tale Story was effective in improving students’ reading skills in eighth grade of SMP Negeri 5 Lirung.